Auctions with costly information acquisition - Jacques Crémer; Yossi Spiegel (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2004)
We consider auction environments in which bidders must incur a cost to learn their valuations and study the optimal selling mechanisms in such environments. These mechanisms specify for each period, as a function of the bids in previous periods, which new potential buyers should be asked to bid. In addition, these mechanisms must induce buyers to both acquire and to reveal truthfully their valuations. Using a generalized Groves principle, we prove a very general full extraction of the surplus result: the seller can obtain the same profit as if he had full control over the buyers' acquisition of information and could have observed directly their valuations once they are informed. We also present appealing implementations of the optimal mechanism in special cases.
Keywords: 330; Auktionstheorie; Informationskosten; Adverse Selection; Mechanism Design